Guidelines for the prophylaxis and treatment of peritoneal metastases from colorectal cancer: a GRADE-approach for evidence evaluation and recommendations - Goéré, Diane; Kusamura, Shigeki; Lurvink, Robin J.; Cinquini, Michela; Piso, Pompiliu; Levine, Edward; Hubner, Martin; Cortés Guiral, Delia; Brandl, Andreas; Spinelli, Antonino; De Hingh, Ignace H. J. T.; Deraco, Marcello (Journal of surgical oncology, 2025)
Colorectal peritoneal metastases (CPM) are common in colorectal cancer patients. This article aims to provide GRADE guidelines for the use of hyperthermic intraperitoneal chemotherapy (HIPEC) in two clinical situations: (1) To determine the value of adjuvant HIPEC for the prevention of CPM in high-risk colorectal cancer patients; (2) to determine the impact on survival of cytoreductive surgery and HIPEC followed by adjuvant systemic chemotherapy as compared to systemic chemotherapy alone in patients with CPM.